2005
DOI: 10.1021/bm050464v
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acrylate-Based Block Copolymers Prepared by Atom Transfer Radical Polymerization as Matrices for Paclitaxel Delivery from Coronary Stents

Abstract: Acrylate-based block copolymers, synthesized by atom transfer radical polymerization (ATRP) processes, were evaluated as drug delivery matrices for the controlled release of paclitaxel from coronary stents. The polymers were multiblock copolymers consisting of poly(butyl acrylate) or poly(lauryl acrylate) soft blocks and hard blocks composed of poly(methyl methacrylate), poly(isobornyl acrylate), or poly(styrene) homo- or copolymers. Depending on the ratio of hard to soft blocks in the copolymers, coating form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 20 publications
0
50
0
Order By: Relevance
“…Richard et al reported that paclitaxel preferentially resides in the poly(n-butyl acrylate) (PBA) phase of poly(methyl methacrylate-block-n-butyl acrylate-block-methyl methacrylate) (PMMA-b-PBA-b-PMMA)) triblock copolymers. 23 In contrast, Cho et al found that the paclitaxel segregated to the PMMA phase in the triblock copolymer of poly(methyl methacrylate-b-isobutylene-b-methyl methacrylate) (PMMA-b-PIB-b-PMMA). 8 The apparent discrepancy between these findings confirms the importance of the interactions between the paclitaxel and different blocks in controlling drug distribution.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Richard et al reported that paclitaxel preferentially resides in the poly(n-butyl acrylate) (PBA) phase of poly(methyl methacrylate-block-n-butyl acrylate-block-methyl methacrylate) (PMMA-b-PBA-b-PMMA)) triblock copolymers. 23 In contrast, Cho et al found that the paclitaxel segregated to the PMMA phase in the triblock copolymer of poly(methyl methacrylate-b-isobutylene-b-methyl methacrylate) (PMMA-b-PIB-b-PMMA). 8 The apparent discrepancy between these findings confirms the importance of the interactions between the paclitaxel and different blocks in controlling drug distribution.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, it is expected that the amorphous paclitaxel will act as an antiplasticizer and enhance the T g of molecularly miscible polymeric formulations when the pure polymer T g is lower than the drug T g . Cho et al 8 and Richard et al 23 observed a continuous increment of T g with increasing paclitaxel concentration *To whom correspondence should be addressed. E-mail: ptmather@ syr.edu.…”
Section: Introductionmentioning
confidence: 99%
“…A free radical polymerization has three principal steps which include: the initiation of the active monomer, propagation or growth of the active (or free radical) chain by sequential addition of monomers, and termination of the active chain to give the final polymer product. Acrylate based block copolymes have been synthesized by atom transfer radical polymerization (ATRP) process [10]. The polymers were multiblock copolymers consisting of poly(butyl acrylate) or poly(lauryl acrylate) soft Acrylic Polymer Dispersion Formulations blocks and hard blocks composed of poly (methymethacrylate), poly (isoborny acrylate), or poly (styrene) homo-or copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…9 For hydrophobic drugs like PTx, it has been shown that release from a stent coating can be modulated effectively by changing the drug loading, introducing excipients, or through blending with other homopolymers or copolymers. [10][11][12] Conventional techniques, such as differential scanning calorimetry (DSC), have been used to evaluate potential drug-polymer interactions and better understand the characteristics of the polymer carrier that control the release of PTx. [13][14][15][16][17] Atomic force microscopy (AFM) is a technique that has proven useful for examining the morphology of stent coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation of AFM images with specific drug release profiles has enhanced the understanding of the PTx-based stent coating systems. [9][10][11][12]18 Similar studies with novel polymeric drug-delivery coatings that exhibit different release profiles can expand the understanding of drug distribution, interactions, and subsequent release from the coating.…”
Section: Introductionmentioning
confidence: 99%